Molecular allergology and its impact in specific allergy diagnosis and therapy. Issue 12 (22nd June 2021) - Barber, Domingo; Diaz‐Perales, Araceli; Escribese, Maria M.; Kleine‐Tebbe, Jörg; Matricardi, Paolo M.; Ollert, Markus; Santos, Alexandra F.; Sastre, Joaquin
Abstract: Progressive knowledge of allergenic structures resulted in a broad availability of allergenic molecules for diagnosis. Component‐resolved diagnosis allowed a better understanding of patient sensitization patterns, facilitating allergen immunotherapy decisions. In parallel to the discovery of allergenic molecules, there was a progressive development of a regulation framework that affected both in vitro diagnostics and Allergen Immunotherapy products. With a progressive understanding of underlying mechanisms associated to Allergen immunotherapy and an increasing experience of application of molecular diagnosis in daily life, we focus in analyzing the evidences of the value provided by molecular allergology in daily clinical practice, with a focus on Allergen Immunotherapy decisions.